PKm Alat Penjernih Air Di Desa Pemangkih Tengah - Abdi Fithria; Adi Rahmadi; Arfa Agustina Rezekiah; Friska Septian Pratiwi (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Clean water is an invaluable need for the residents of Pemangkih Tengah village. The water in the village of Pemangkih Tengah is actually blackish in color, because the area of this village is located in a location with peaty soil and acid soil. To overcome this problem, it is necessary to have a water purification device using materials that are easily available. Materials that are easily available include rice husks, sand, gravel and palm fibers. The goal is that people are more enthusiastic about making their own, because the materials used are around them. Moreover, part of the village land is planted with rice, so that the husks produced from the rice grinder can be used for natural water purification. In contrast to water purification using chemical techniques, natural techniques are preferred by the community because the costs incurred to make tools are cheaper. From the results of the purification that has been carried out, it is clear that there is a difference in the level of water clarity before and after it is done.